Breaking Barriers: Addressing Inequality and Building Equity in Education Systems - Khatib; Fatima Noor (PT Mutiara Bustan Ilmu, 2025)
This study explores the persistent challenges of inequality in education and highlights strategies for fostering equity across diverse learning environments. By adopting a qualitative research design, the study examines barriers that hinder equal access to education, including socioeconomic disparities, cultural differences, and systemic biases. The research further investigates the role of teachers, policymakers, and communities in promoting fairness and inclusivity within educational systems. Findings suggest that equity-driven approaches—such as culturally responsive pedagogy, resource redistribution, and inclusive policies—can significantly enhance student participation and outcomes. Additionally, the study underscores the importance of collaboration between schools, governments, and society to build sustainable frameworks that ensure equal opportunities for all learners. Ultimately, this research contributes to ongoing global discussions on social justice in education by offering practical insights for transforming schools into more equitable institutions.